2018
DOI: 10.1177/1971400917751036
|View full text |Cite
|
Sign up to set email alerts
|

Sella turcica bridging and ossified carotico-clinoid ligament: Correlation with sex and age

Abstract: Aim Sella turcica bridging and ossified carotico-clinoid ligament are two variants of the sella turcica, the origin of which is partially unknown. These variations should be properly recognised, as they may hamper the removal of the anterior clinoid process in surgical procedures. Therefore, our aim was to determine the prevalence of these two anatomical variants and to investigate their prevalence according to patient sex and age in a series of maxilla computed tomography scans. Materials and methods We revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
(92 reference statements)
1
13
0
Order By: Relevance
“…The incidence of interclinoid ligamentous mineralisation was higher in the current study than in many prior studies (4–11.8% [ 2 , 12 , 26 , 27 , 29 , 36 , 37 , 39 ]), which may be secondary to the relatively long and exposed nature of the interclinoid ligament that could make it vulnerable to loss during the preparation of dry skulls. Indeed, a large Italian study of 300 CT scans of the head recorded incidences closer to the current study; furthermore, it corroborated our observation that mineralisation of the caroticoclinoid and interclinoid ligaments is not infrequently associated [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The incidence of interclinoid ligamentous mineralisation was higher in the current study than in many prior studies (4–11.8% [ 2 , 12 , 26 , 27 , 29 , 36 , 37 , 39 ]), which may be secondary to the relatively long and exposed nature of the interclinoid ligament that could make it vulnerable to loss during the preparation of dry skulls. Indeed, a large Italian study of 300 CT scans of the head recorded incidences closer to the current study; furthermore, it corroborated our observation that mineralisation of the caroticoclinoid and interclinoid ligaments is not infrequently associated [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“… Erturk, Kayalioglu, and Govsa [ 31 ] 119 dry skulls + 52 cadaveric heads Turkey 8.18% Neurosurgical implications and relationship with cavernous sinus. Gibelli et al [ 32 ] 300 CT head scans Italy 18–99 years 16.00% Association between interclinoid and caroticoclinoid bridging. Potential association with interclinoid mineralisation and age.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a partially or completely calcified bridge of the sella turcica in subjects with altered direction of dental eruption, currently provides a genetic-based further evidence for subjects affected of these conditions. As sella turcica bridging occurs early during the developmental period, it has been suggested as a screening test for possible genetic diseases and dental alterations (25). Certainly, the findings of this study indicate that subjects with sella turcica bridging have a potential risk of developing alterations of dental eruption direction.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found a correlation between sella turcica bridging and age. In a study of northern Italian patients 300, in which 300 computed tomography scans of the head were revised, the prevalence of sella turcica bridging was 16% (25). Significant differences according to sex were not found, which is in agreement with our study, but a correlation with age was observed ( P = 0.007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation